Combination targeting of subthalamic nucleus and ventral intermediate thalamic nucleus with a single trajectory in deep brain stimulation for tremor-dominant Parkinson's disease. (March 2021) - Fayed, Islam; Cobourn, Kelsey D.; Pivazyan, Gnel; Torres-Yaghi, Yasar A.; Pagan, Fernando L.; Lo, Steven E.; Mandir, Allen S.; Kalhorn, Christopher G.
Highlights: STN and VIM can be targeted with a single trajectory in tremor-dominant PD patients. UPDRS, LEDD and tremor scores decreased by 38.2%, 40.2% and 59.0%, respectively. One patient had transient left-sided weakness, yielding a 5.3% complication rate. Larger studies may validate this as the optimal DBS target in tremor-dominant PD. Abstract: Deep brain stimulation (DBS) has traditionally been used to target the subthalamic nucleus (STN) or globus pallidus internus (GPi) to treat Parkinson's disease (PD) and the ventral intermediate thalamic nucleus (VIM) to treat essential tremor (ET). Recent case reports have described targeting both the STN and VIM with a single trajectory and electrode to treat patients with tremor-dominant PD, yet outcome data for this procedure remains sparse. Our objective is to determine the safety and efficacy of combination STN-VIM DBS. We conducted a single-center retrospective case series of all patients who underwent combined STN-VIM DBS. Demographic, perioperative, and outcome data, including Unified Parkinson Disease Rating Scale-III (UPDRS) and tremor scores (OFF-medication), and levodopa equivalent daily dose (LEDD), were collected and analyzed. Nineteen patients underwent this procedure. Patients were 89% male and 11% female, with a mean age of 63.6 years. Mean preoperative UPDRS was 24.1, and LEDD was 811.8. At a mean follow-up of 33.8 months, UPDRS and LEDD decreased by an average of 9.2 (38.2%) and 326.3 (40.2%), respectively. Tremor scores decreased by 4.9 (59.0%), and 58% were able to decrease total medication burden. One patient developed transient left-sided weakness, yielding a complication rate of 5.3%. Combined targeting of STN and VIM thalamus via a single frontal trajectory for tremor-dominant Parkinson's Disease results in similar UPDRS outcomes to STN DBS and improved control of tremor symptoms. Larger multicenter studies are necessary to validate this as the optimal DBS target for tremor-dominant PD.